A study on the relationship between job satisfaction and affective commitment among support staff in selected public sector departments in Bandar Permaisuri, Terengganu / Norul Hidayati Muhamad Nor - Muhamad Nor, Norul Hidayati (2016)
This research paper was aimed to investigate the correlation between job satisfaction and affective commitment among support staff at selected public sector departments in Bandar Permaisuri, Terengganu. 56 respondents completed the survey questionnaire which was adopted from Web survey master (2016), Spector (1994), Maslic (1999) and Jaros (2007). This study used disproportionate stratified random sampling technique and the response rate was 85.7%. SPSS V-20 was used to analyze the questionnaires in order to determine the result. Most of the respondents were male workers, age between 31 to 40 and have 5 to 10 years work experience. The findings showed that there was very strong positive relationship between job satisfaction and affective commitment (r=.869, p=0.00). Moreover, there were very strong positive correlation between salary and affective commitment (r=.944, p=.000) as well as with fringe benefits (r=.700, p=.000). However, the finding indicates the correlation was insignificant for promotion (r=.258, p=0.77). The value of R Square showed that 94.1% of the variance in job satisfaction can be predicted from the variable of salary, fringe benefits and promotion. The regression model consisting of salary, fringe benefits and promotion towards affective commitment was significant at 0.05 level F (3, 44) = 235.87, P < .05. However, there is no correlation between years of experience and affective commitment as r=.203, p=.167. It is recommended that the management equip all the workers with training and improve supervision in order to increase their affective commitment. Future research should conduct a study to other industry and cover a large number of respondents in order to gain a comprehensive and reliable result of analysis.